Seeing with free eyes the poetic justice of Euripides - Sokolon, Marlene K. (SUNY series in ancient Greek philosophy., 2021)
"Examines the ideas of justice in Euripidean tragedy, which reveals the human experience of justice to be paradoxical, and reminds us of the need for humility in our unceasing quest for a just world"--